2022
DOI: 10.1037/bne0000498
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates restraint stress-induced learning and memory deficit and activity via modulation of biochemical, morphology changes, and apoptosis in the prefrontal cortex and hippocampus.

Abstract: Restraint stress indicated induction of morphology, biochemistry, and behavioral impairments. Several investigations have reported that curcumin has a protective effect against stress disturbance. The present study is designed to investigate the effects of curcumin on learning and memory, activity, biochemical, morphology changes, and apoptosis in the hippocampus and prefrontal cortex of restraint stress rats. For chronic restraint stress, the rats were kept in the restrainers for 2.5 h per day for 21 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The findings of the present study demonstrated that chronic stress significantly enhanced MDA levels, accompanied by decreased levels of the major antioxidant enzymes, SOD and CAT, in the hippocampus; these findings are consistent with those of previous studies (41,42). According to previous findings, the supplementation of natural compounds can ameliorate learning and memory deficits involved in the CRS-induced production of oxidative stress (37,43). Pinostrobin exhibits a several of pharmacological activities, such as antioxidant, anti-inflammatory and neuroprotective properties (21)(22)(23).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of the present study demonstrated that chronic stress significantly enhanced MDA levels, accompanied by decreased levels of the major antioxidant enzymes, SOD and CAT, in the hippocampus; these findings are consistent with those of previous studies (41,42). According to previous findings, the supplementation of natural compounds can ameliorate learning and memory deficits involved in the CRS-induced production of oxidative stress (37,43). Pinostrobin exhibits a several of pharmacological activities, such as antioxidant, anti-inflammatory and neuroprotective properties (21)(22)(23).…”
Section: Discussionsupporting
confidence: 93%
“…According to previous findings, the supplementation of natural compounds can ameliorate learning and memory deficits involved in the CRS-induced production of oxidative stress ( 37 , 43 ). Pinostrobin exhibits a several of pharmacological activities, such as antioxidant, anti-inflammatory and neuroprotective properties ( 21-23 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation